(untitled) (Scientific electronic journal "Labor Economics and Human Capital", 2024)
In the article, as a result of the economic reforms being carried out in our country to develop the agricultural sector, proposals are put forward to focus attention on the issues of training personnel in the insurance sector. This article studies the reforms carried out in the field of agricultural insurance, training of qualified personnel to provide insurance services, and analyzes the availability of personnel working in the insurance sector on the basis of statistical data. Recommendations are given for the development of the agricultural sector based on modern approaches to training qualified personnel in the insurance sector.